2002
DOI: 10.1097/00004770-200210000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Endodontic Sealers to Dentin and Gutta-Percha

Abstract: Adhesion of endodontic sealers to dentin and gutta-percha offers clues into their interaction with the wall of the root canal and the filling material. In this in vitro study, four classes of endodontic sealers (Kerr, a ZOE-based sealer; Sealapex, a calcium hydroxide-based sealer; AH 26, an epoxy resin-based system; and Ketac-Endo, a glass-ionomer based sealer) were compared for their ability to bond to dentin or gutta-percha. Flat coronal dentin or gutta-percha surfaces were created by using a diamond-impregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
205
4
24

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(261 citation statements)
references
References 15 publications
8
205
4
24
Order By: Relevance
“…To achieve a dense, three-dimensional obturation, gutta percha cones must be used with root canal sealers. Root canal sealers not only provide adhesion to both gutta percha and root dentin 6) , they also fi ll the voids and minor discrepancies between gutta percha cones and root canal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve a dense, three-dimensional obturation, gutta percha cones must be used with root canal sealers. Root canal sealers not only provide adhesion to both gutta percha and root dentin 6) , they also fi ll the voids and minor discrepancies between gutta percha cones and root canal wall.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a hermetic seal, gutta percha is typically used in conjunction with root canal sealers because gutta percha is incapable of bonding to root canal walls. Root canal sealers not only fi ll the voids between gutta percha points, they also fi ll the voids between gutta percha and root canal walls 6) . Bondable root canal sealers purportedly improve the seal and fracture resistance of endodontically treated roots 7,8) .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, calcium hydroxide based sealers showed poor dentin adhesion [32][33][34][35]. One study showed calcium hydroxide based sealer (Apexit) inhibited Gram negative bacteria more effectively than gram positive bacteria [36].…”
Section: Methodsmentioning
confidence: 99%
“…Gutta-percha is typically used with a root canal sealer to obtain a fluid-tight seal. Root canal sealers fill the voids between gutta-percha points and between gutta-percha and root canal walls (2).…”
Section: Introductionmentioning
confidence: 99%